High-activity and high-strength bio-based composite membrane and preparation method thereof
By introducing strengthening modifiers such as plant polyphenols and multivalent metal ions into the biomatrix composite membrane, a multiple cross-linking network was built, and ultrasonic stirring technology was used to solve the problem of low mechanical strength of the biomatrix composite membrane and achieve high activity High-strength biomass composite membranes have expanded their application areas and reduced environmental pollution.
Patent Information
- Application Number
- CN202411663152.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
AI Technical Summary
The mechanical strength of existing biomass composite membranes is generally low, making it difficult to have excellent biological activity and mechanical properties, and there is also potential safety risks brought about by the use of petroleum-based aldehyde compounds.
By using plant polyphenols as bioactive reagents, and introducing enhancement modifiers such as bio-based aldehydes or multivalent metal ions, as well as interface compatibilizers such as functionalized graphene, a multiple crosslinking network is constructed, and the enhanced homogeneity effect of ultrasonic stirring is enhanced by the enhancement of ultrasonic stirring , improve the antioxidant activity and mechanical strength of biomass composite membranes.
It significantly improves the mechanical properties and antioxidant activity of biomass composite membranes, gives it higher application value, expands its application potential in food packaging, biomedicine and other fields, and reduces environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite membrane manufacturing, and in particular to a high-activity and high-strength bio-based composite membrane and a preparation method thereof. Background Art
[0002] At present, membrane materials made from petroleum-based chemicals have been widely used in people's daily lives. As a non-renewable resource, the reserves of petroleum are gradually decreasing. The production of petroleum-based membrane materials is highly dependent on petroleum resources, which undoubtedly exacerbates the increasing shortage of petroleum resources. From an environmental perspective, petroleum-based membrane materials are difficult to degrade in the natural environment due to their stable chemical structure. A large amount of discarded petroleum-based membrane materials accumulate in the soil, which will hinder the air permeability and water permeability of the soil and affect the growth of vegetation; if they enter the water body, they will decompose into microplastics, endanger aquatic life, and then affect the entire ecosystem through the food chain. These problems seriously threaten the ecological balance and sustainable development of mankind.
[0003] In this context, the research and development of bio-based membranes is of vital importance. Bio-based membranes use renewable biomass resources as their main raw materials, such as plant fibers and starch, which reduces dependence on petroleum resources from the source and helps alleviate the pressure of resource shortages. Moreover, bio-based membranes are biodegradable and can be decomposed into harmless substances by microbial action in the natural environment after being discarded, thereby reducing pollution to the environment. This has a positive supporting role in the realization of the country's "carbon neutrality" strategy and "dual carbon" goals. On the one hand, the carbon emissions in the production process of bio-based membranes are relatively low; on the other hand, their degradability avoids the production of greenhouse gases in the long-term degradation process of discarded membranes, which helps to reduce carbon footprints and promote the coordinated development of energy structure optimization and environmental protection. In addition, bio-based membranes also play an important role in the country's "big health" strategy. In the field of medical and food packaging, the use of bio-based membranes can reduce the risk of chemical migration caused by petroleum-based membranes and reduce potential harm to human health. For example, in food packaging, bio-based film materials can prevent harmful substances from penetrating into food and ensure food safety; in the medical field, their good biocompatibility is conducive to the development of safer and more environmentally friendly medical devices and medical dressings.
[0004] At present, active bio-based functional membranes are mainly prepared by introducing various active substances into natural polymer matrices and using solution casting, such as antibacterial membranes, antioxidant membranes, etc. However, under the existing technical system, the mechanical strength of the prepared composite membranes is generally low, and it is difficult to have both excellent biological activity and mechanical properties. In addition, there are potential safety risks caused by the use of petroleum-based aldehyde compounds, which greatly limits its application in the fields of active packaging materials. Summary of the invention
[0005] The purpose of the present invention is to provide a high-activity and high-strength bio-based composite membrane and its preparation method in order to solve the problems of high toxicity caused by the use of conventional petroleum-based aldehyde compounds, poor dispersion of functional components in the bio-based polymer matrix, and difficulty in fully exerting functional effects in the preparation of bio-based composite membranes. The present invention uses plant polyphenols as bioactive agents; at the same time, introduces reinforcing modifiers such as bio-based aldehydes or multivalent metal ions and interface compatibilizers such as functionalized graphene, and through the multiple combination of the above two functional components with bio-based polymers and plant polyphenols, and the enhanced homogenization effect of ultrasonic stirring, the antioxidant activity and mechanical strength of the bio-based composite membrane are effectively improved, giving it a higher application value.
[0006] To achieve the above object, the first technical solution provided by the present invention is: A high-activity and high-strength bio-based composite membrane, wherein the raw materials include a bio-based polymer with good film-forming properties, a plant polyphenol with multiple phenolic hydroxyl groups, a reinforcing modifier, an interface compatibilizer, and a plasticizer mixed in a weight ratio of 100:(2-10):(0.5-1.0):(0.5-5):(10-30); wherein the reinforcing modifier includes at least one of a bio-based aldehyde and a multivalent metal ion.
[0007] Preferably, the plant polyphenols having multiple phenolic hydroxyl groups include at least one of hydrolyzable tannins, condensed tannins and small molecule plant-based phenolic acids.
[0008] Preferably, the bio-based polymer with good film-forming properties includes at least one of collagen, gelatin, chitosan, cellulose and its derivatives, starch and its derivatives, sodium alginate and xanthan gum.
[0009] Preferably, the interfacial compatibilizer includes at least one of carboxylated graphene, aminolated graphene and a silane coupling agent.
[0010] Preferably, the plasticizer is polyol and its ester derivatives.
[0011] More preferably, the plasticizer includes at least one of glycerol, sorbitol and isosorbide.
[0012] Preferably, the multivalent metal ions include at least one metal ion selected from the group consisting of aluminum, iron, cerium, gadolinium, praseodymium and lanthanum.
[0013] The second technical solution adopted by the present invention is: The method for preparing a high-activity and high-strength bio-based composite membrane comprises the following steps: after uniformly mixing the raw materials, reacting them under ultrasonic stirring at a pH of 2.0-4.5 and a temperature of 25-40°C for 0.5-2 h, and then preparing the high-activity and high-strength bio-based composite membrane by a solution casting method.
[0014] In view of the problem that the mechanical strength of conventional bio-based composite membranes is generally low, the present invention proposes to construct a multiple cross-linked network in the matrix structure of the bio-based composite membrane, and realize effective bonding between the components through multi-point hydrogen bonding and covalent / coordinate bonding between plant polyphenols, bio-based polymers, strengthening modifiers and interfacial compatibilizer molecules, thereby improving the cross-linking density and strength of the composite membrane and enhancing the mechanical properties of the composite membrane. At the same time, with the help of the strong cavitation effect of ultrasonic stirring, the molecules of each component are forced to move violently, generating unidirectional forces to accelerate the mutual transmission and diffusion between the components, achieving the homogenization of the functional components, and improving the uniformity of the multiple cross-linked network, thereby significantly improving the mechanical properties of the bio-based composite membrane. At the same time, through the selection of strengthening modifiers, the biological activity of the plant polyphenols can be increased, and finally it is given a higher application value.
[0015] The technical solution provided by the present invention has the following beneficial effects: (1) The present invention uses biomass as the main raw material, introduces functional components, and constructs a multiple multi-point cross-linking network, thereby achieving strength improvement and functionalization of the bio-based composite film, expanding its application potential in food packaging, biomedicine and other fields, and having good economic benefits.
[0016] (2) The main component of the bio-based composite membrane provided by the present invention is biomass raw materials, which are renewable and biodegradable. After being discarded, they will not cause "white pollution" to the environment, and therefore have good environmental and social benefits. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, some non-essential improvements and adjustments made by technicians in the field to the present invention according to the content of the present invention should still fall within the protection scope of the present invention.
[0018] The first embodiment of the present invention provides a high-activity and high-strength bio-based composite membrane, the raw materials of which include a bio-based polymer with good film-forming properties, a plant polyphenol with multiple phenolic hydroxyl groups, a reinforcing modifier, an interface compatibilizer, and a plasticizer mixed in a weight ratio of 100:(2~10):(0.5~1.0):(0.5~5):(10~30); wherein the reinforcing modifier includes at least one of a bio-based aldehyde and a polyvalent metal ion.
[0019] The present invention realizes effective bonding between the components through multi-point hydrogen bonding and covalent / coordinate bonding between plant polyphenols, bio-based polymers, reinforcing modifiers and interface compatibilizer molecules, thereby improving the crosslinking density and strength of the composite film and enhancing the mechanical properties of the composite film. At the same time, after the multivalent metal ions and plant polyphenols are coordinated and assembled, functional nanoparticles can be formed to exert a synergistic effect and enhance the antioxidant activity of the composite film.
[0020] It should be noted that, since the present invention is a membrane material, any bio-based polymer with good film-forming properties can be applied to the present invention as a matrix membrane material to achieve the effect of the present invention. For example, it can include at least one of collagen, gelatin, chitosan, cellulose and its derivatives, starch and its derivatives, sodium alginate and xanthan gum.
[0021] As for plant polyphenols, as long as they have multiple phenolic hydroxyl groups, they can be applied to the present invention to achieve the effects of the present invention. For example, they can include at least one of hydrolyzed tannins, condensed tannins, and small molecular plant-based phenolic acids. The principle is that the multiple phenolic hydroxyl groups on the plant polyphenols can form hydrogen bonds with hydroxyl groups, amino groups, etc. on bio-based polymers on the one hand, and can react with multivalent metal ions on the other hand to form coordinated cross-linking bonds, and can further promote the assembly of plant polyphenols into nanoparticles to achieve the gain of the biological activity of plant polyphenols.
[0022] As for the interfacial compatibilizer, any interfacial compatibilizer that can form hydrogen bonds or other bonding effects with the matrix polymer can achieve the effect of the present invention. For example, it can include at least one of carboxylated graphene, amino graphene and silane coupling agent.
[0023] As for the plasticizer, any plasticizer commonly used in the art, and any plasticizer having good compatibility with the matrix polymer can achieve the effect of the present invention, generally polyols and their ester derivatives. For example, it can include at least one of glycerol, sorbitol and isosorbide ester.
[0024] As the reinforcing modifier, only at least one of the bio-based aldehydes may be used, only at least one of the polyvalent metal ions may be used, or both the bio-based aldehydes and the polyvalent metal ions may be used.
[0025] Among them, the multivalent metal ions generally include at least one metal ion selected from aluminum, iron, cerium, gadolinium, praseodymium, and lanthanum, which can form coordinated cross-linking bonds with bio-based polymers, plant polyphenols, and interfacial compatibilizers, giving the composite membrane matrix a denser cross-linked network structure and improving the strength of the composite membrane. In addition, the multivalent metal ions can also promote the assembly of plant polyphenols into nanoparticles, thereby increasing the biological activity of plant polyphenols. In the preparation process of composite membranes, the multivalent metal ions are generally salts corresponding to metal ions, such as nitrates, acetates, etc.
[0026] The second embodiment of the present invention provides a method for preparing a high-activity and high-strength bio-based composite membrane. After the raw materials are evenly mixed, they are reacted under ultrasonic stirring for 0.5 to 2 h at a pH of 2.0 to 4.5 and a temperature of 25 to 40 ° C, and then a solution casting method is used to prepare a high-activity and high-strength bio-based composite membrane.
[0027] It should be noted that the order of adding the raw materials when mixing in the above preparation process does not affect the final effect. The pH during the reaction is determined based on the requirement that the plant polyphenols, bio-based polymers, reinforcing modifiers and interfacial compatibilizer molecules can form multi-point hydrogen bonds and covalent / coordinate bonds, while ensuring that the molecules of each component are not oxidized.
[0028] In order to make the technical solution of the present invention clearer, the bio-based composite and its performance are described in detail through multiple specific embodiments below.
[0029] It is also worth noting that: In the following examples, "parts" refer to "parts by weight".
[0030] Example 1 Take 100 parts of gelatin, add it to 1000 parts of water, stir and dissolve it at 50°C to obtain a gelatin solution, then add 2 parts of gallotannin, 0.5 parts of cerium nitrate, 0.5 parts of carboxylated graphene and 30 parts of propylene glycol in sequence under stirring, adjust the pH to 2.0, and react the mixed solution under ultrasonic stirring at 25°C for 1 h. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a high-activity and high-strength bio-based composite membrane.
[0031] Example 2 Take 100 parts of chitosan, add it to 1000 parts of acetic acid aqueous solution, stir and dissolve it at 50°C to obtain chitosan solution, then add 4 parts of bayberry tannin, 0.5 parts of dialdehyde sucrose, 1 part of amino graphene and 25 parts of sorbitol in sequence under stirring, adjust the pH to 4.5, and react the mixed solution at 30°C for 1.5 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a high-activity and high-strength bio-based composite membrane.
[0032] Example 3 Take 100 parts of cellulose, add it to 1000 parts of water, stir and disperse it at 50°C to obtain a cellulose dispersion, then add 2 parts of catechin, 0.8 parts of gadolinium nitrate, 5 parts of γ-glycidyloxypropyl trimethoxysilane and 20 parts of isosorbide in sequence under stirring, adjust the pH to 3.5, and react the mixed solution at 40°C for 2 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a high-activity and high-strength bio-based composite membrane.
[0033] Example 4 Take 100 parts of sodium carboxymethyl cellulose and add it to 1000 parts of water. After fully stirring and dissolving at 50°C, a sodium carboxymethyl cellulose solution is obtained. Then, 8 parts of tara tannin, 1 part of cerium nitrate, 2 parts of carboxylated graphene and 30 parts of propylene glycol are added in sequence under stirring. The pH is adjusted to 2.5, and the mixed solution is reacted at 35°C for 0.5 h under ultrasonic stirring. Finally, the reaction solution is poured onto a polytetrafluoroethylene mold, left to dry naturally, and peeled off to obtain a highly active and high-strength bio-based composite membrane.
[0034] Example 5 Take 100 parts of sodium carboxymethyl starch, add it to 1000 parts of water, stir and dissolve it at 50°C to obtain sodium carboxymethyl starch solution, then add 6 parts of gallic acid, 1 part of aluminum chloride, 3 parts of carboxylated graphene and 20 parts of isosorbide ester in sequence under stirring, adjust the pH to 3.0, and react the mixed solution at 40°C for 0.5 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a high-activity and high-strength bio-based composite membrane.
[0035] Example 6 Take 100 parts of sodium alginate and add it to 1000 parts of water. After fully stirring and dissolving at 50°C, a sodium alginate solution is obtained. Then, 4 parts of rubber acid, 1 part of cerium diamine nitrate, 0.5 parts of carboxylated graphene and 30 parts of isosorbide are added in sequence under stirring. The pH is adjusted to 4.0, and the mixed solution is reacted at 40°C under ultrasonic stirring for 1.5 h. Finally, the reaction solution is poured onto a polytetrafluoroethylene mold, left to dry naturally, and peeled off to obtain a highly active and high-strength bio-based composite membrane.
[0036] Example 7 Take 100 parts of starch and add it to 1000 parts of water. After gelatinization and stirring to dissolve, a starch dispersion is obtained. Then, 10 parts of wattle bark tannin, 0.6 parts of dialdehyde dextrin, 4 parts of aminoethylaminopropyl triethoxysilane and 10 parts of isosorbide are added in sequence under stirring, and the pH is adjusted to 4.5. The mixed solution is reacted at 40°C under ultrasonic stirring for 0.5 h. Finally, the reaction solution is poured onto a polytetrafluoroethylene mold, left to dry naturally, and peeled off to obtain a highly active and high-strength bio-based composite membrane.
[0037] Example 8 Take 100 parts of xanthan gum and add it to 1000 parts of water. After fully stirring and dissolving at 50°C, a xanthan gum solution is obtained. Then, 4 parts of gallic acid, 1 part of lanthanum nitrate, 0.6 parts of carboxylated graphene and 30 parts of propylene glycol are added in sequence under stirring, and the pH is adjusted to 3.0. The mixed solution is reacted at 30°C for 1 h under ultrasonic stirring. Finally, the reaction solution is poured onto a polytetrafluoroethylene mold, dried naturally, and peeled off to obtain a highly active and high-strength bio-based composite membrane.
[0038] Example 9 Take 50 parts of gelatin and 50 parts of chitosan, add them to 1000 parts of acetic acid aqueous solution, stir and dissolve them at 50°C to obtain gelatin-chitosan solution, then add 2 parts of epicatechin, 0.5 parts of dialdehyde sodium alginate, 0.5 parts of amino graphene and 30 parts of propylene glycol in sequence under stirring, adjust the pH to 2.5, and react the mixed solution at 40°C for 0.5h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a high-activity and high-strength bio-based composite membrane.
[0039] Example 10 Take 50 parts of gelatin and 50 parts of chitosan, add them to 1000 parts of acetic acid aqueous solution, stir and dissolve them at 50°C to obtain gelatin-chitosan solution, then add 4 parts of gallcatechin, 2 parts of dialdehyde sucrose, 5 parts of 3-aminopropyl triethoxysilane and 15 parts of sorbitol in sequence under stirring, adjust the pH to 4.5, and react the mixed solution at 40°C for 2 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a high-activity and high-strength bio-based composite membrane.
[0040] Embodiment 11 Take 100 parts of gelatin, add it to 1000 parts of water, stir and dissolve it at 50°C to obtain a gelatin solution, then add 2 parts of epicatechin, 0.5 parts of sodium dialdehyde alginate, 0.5 parts of cerium acetate, 0.5 parts of carboxylated graphene, 15 parts of glycerol and 15 parts of sorbitol in sequence under stirring, adjust the pH to 4.0, and react the mixed solution at 30°C for 1.5 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a high-activity and high-strength bio-based composite membrane.
[0041] Example 12 Take 100 parts of chitosan, add it to 1000 parts of acetic acid aqueous solution, stir and dissolve it at 50°C to obtain chitosan solution, then add 2 parts of catechin, 2 parts of gallic acid, 1 part of gadolinium nitrate, 1 part of dialdehyde sucrose, 0.5 parts of amino graphene, 0.5 parts of 3-aminopropyltrimethoxysilane and 30 parts of glycerol in sequence under stirring, adjust the pH to 4.0, and react the mixed solution at 40°C for 0.5 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a high-activity and high-strength bio-based composite membrane.
[0042] Embodiment 13 Take 100 parts of gelatin, add it to 1000 parts of water, stir and dissolve it at 50°C to obtain a gelatin solution, then add 4 parts of gallic acid, 0.5 parts of praseodymium nitrate, 1 part of carboxylated graphene and 30 parts of propylene glycol in sequence under stirring, adjust the pH to 3.0, and react the mixed solution at 40°C for 2 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain an active high-strength bio-based composite membrane.
[0043] Embodiment 14 Take 100 parts of sodium carboxymethyl cellulose and add it to 1000 parts of water. After fully stirring and dissolving at 50°C, a gelatin solution is obtained. Then, 4 parts of gallic acid, 0.5 parts of erbium nitrate, 1 part of carboxylated graphene and 30 parts of propylene glycol are added in sequence under stirring, and the pH is adjusted to 2.0. The mixed solution is reacted at 30°C for 1 h under ultrasonic stirring. Finally, the reaction solution is poured onto a polytetrafluoroethylene mold, left to dry naturally, and peeled off to obtain a highly active and high-strength bio-based composite membrane.
[0044] Embodiment 15 Take 100 parts of gelatin, add it to 1000 parts of water, stir and dissolve it at 50°C to obtain a gelatin solution, then add 8 parts of oxalic acid, 1.5 parts of ytterbium nitrate, 0.5 parts of cerium acetate, 1 part of amino graphene and 20 parts of sorbitol in sequence under stirring, adjust the pH to 4.0, and react the mixed solution at 30°C for 2 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a highly active and high-strength bio-based composite membrane.
[0045] Example 16 Take 100 parts of collagen, add it to 1000 parts of acetic acid aqueous solution, stir and dissolve it at 50°C to obtain gelatin solution, then add 2 parts of gallic acid, 0.5 parts of praseodymium nitrate, 0.5 parts of cerium nitrate, 1 part of carboxylated graphene and 30 parts of propylene glycol in sequence under stirring, adjust the pH to 2.5, and react the mixed solution at 40°C for 1 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a highly active and high-strength bio-based composite membrane.
[0046] Comparative Example 1 Compared with Example 1, the only difference is that the addition of gallotannin is eliminated, and the remaining raw materials and preparation method are the same as those in Example 1, specifically: Take 100 parts of gelatin, add it to 1000 parts of water, stir and dissolve it at 50°C to obtain a gelatin solution, then add 0.5 parts of cerium nitrate, 0.5 parts of amino graphene and 30 parts of propylene glycol in sequence under stirring, adjust the pH to 2.0, and react the mixed solution under ultrasonic stirring at 25°C for 1 h. Finally, pour the mixed solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a bio-based composite membrane.
[0047] Comparative Example 2 Compared with Example 12, the only difference is that the addition of gadolinium nitrate and dialdehyde sucrose is eliminated, and the remaining raw materials and preparation method are the same as those of Example 12, specifically: Take 100 parts of chitosan, add it to 1000 parts of acetic acid aqueous solution, stir and dissolve it at 50°C to obtain chitosan solution, then add 2 parts of catechin, 2 parts of gallic acid, 0.5 parts of amino graphene, 0.5 parts of 3-aminopropyltrimethoxysilane and 30 parts of glycerol in sequence under stirring, adjust the pH to 4.0, and react the mixed solution at 40°C for 0.5 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a bio-based composite membrane.
[0048] Comparative Example 3 Compared with Example 12, the only difference is that the dosage of catechin and gallic acid is reduced, and the other raw materials and preparation method are the same as those of Example 12, specifically: Take 100 parts of chitosan, add it to 1000 parts of acetic acid aqueous solution, stir and dissolve it at 50°C to obtain chitosan solution, then add 0.5 parts of catechin, 0.5 parts of gallic acid, 1 part of gadolinium nitrate, 1 part of dialdehyde sucrose, 0.5 parts of amino graphene, 0.5 parts of 3-aminopropyltrimethoxysilane and 30 parts of glycerol in sequence under stirring, adjust the pH to 4.0, and react the mixed solution at 40°C for 0.5 h under ultrasonic stirring. Finally, pour the reaction solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a bio-based composite membrane.
[0049] Comparative Example 4 Take 100 parts of gelatin, add it to 1000 parts of water, stir and dissolve it at 50°C to obtain a gelatin solution, then add 4.0 parts of amino graphene, 12 parts of dialdehyde sodium alginate and 40 parts of propylene glycol in sequence under stirring, adjust the pH to 8.5, and place the mixed solution on a tumbling oscillator at 80°C for 8 h. Finally, pour the mixed solution on a polytetrafluoroethylene mold, let it dry naturally, and peel it off to obtain a bio-based composite membrane.
[0050] The antioxidant activity, water vapor permeability and mechanical strength of the bio-based composite membranes prepared in Examples 1-16 and Comparative Examples 1-4 were tested and compared. The results are shown in Table 1.
[0051] Table 1 Comparison of performance of bio-based composite membranes .
[0052] As can be seen from Table 1, the bio-based composite films provided by Comparative Examples 1, 3 and 4 have low antioxidant activity and tensile strength. The bio-based composite films provided by Examples 1 to 16 have high free radical scavenging activity and high tensile strength at the same time. Importantly, compared with the technical solution provided by Comparative Example 2, the introduction of cerium nitrate, sodium dialdehyde alginate and carboxylated graphene in the embodiment of the present invention significantly improves the antioxidant activity and mechanical strength of the bio-based composite film. This shows that the addition of selected reinforcing modifiers such as multivalent metal ions can increase the biological activity of plant polyphenols and improve the mechanical strength of the composite film. Among them, the multivalent metal ions can form a coordination bonding network between bio-based polymers, plant polyphenols, sodium dialdehyde alginate and carboxylated graphene, making the cross-linked network of the composite film matrix denser, thereby significantly improving the mechanical strength of the composite film; at the same time, after the multivalent metal ions are coordinated and assembled with the plant polyphenols, functional nanoparticles can also be formed to exert a synergistic effect and enhance the antioxidant activity of the composite film. Compared with the four comparative examples, the bio-based composite membranes provided in the embodiments have lower water vapor permeability. This is because the introduction of reinforcing modifiers and interfacial compatibilizers can increase the cohesion between bio-based polymer chains, and the strong cavitation effect of ultrasonic stirring can promote the uniform bonding between the components of the composite membrane, thereby reducing the free volume of the composite membrane matrix and improving the structural density of the composite membrane, thereby achieving the effect of reducing water vapor permeation.
[0053] In summary, by adopting the raw materials and preparation methods of the embodiments of the present invention, not only can the bio-based composite film be endowed with good biological activity, but also excellent mechanical strength can be given to it at the same time, so as to realize the preparation of active and high-strength bio-based composite films, and greatly enhance its application potential in different fields. In addition, the main raw materials of the composite film provided by the present invention are derived from green and low-carbon bio-based polymers, which can endow the composite film with excellent biodegradability, and help reduce and promote the realization of my country's "dual carbon" strategic goals.
[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. Highly active and high-strength bio-based composite membrane, characterized in that: The raw materials include a bio-based polymer with good film-forming properties, a plant polyphenol with multiple phenolic hydroxyl groups, a reinforcing modifier, an interface compatibilizer, and a plasticizer, which are mixed in a weight ratio of 100:(2-10):(0.5-1.0):(0.5-5):(10-30); wherein the reinforcing modifier includes at least one of a bio-based aldehyde and a multivalent metal ion.
2. The highly active and high-strength bio-based composite membrane according to claim 1, characterized in that: The plant polyphenols having a plurality of phenolic hydroxyl groups include at least one of hydrolyzable tannins, condensed tannins and small-molecule plant-based phenolic acids.
3. The highly active and high-strength bio-based composite membrane according to claim 1, characterized in that: The bio-based polymer with good film-forming property includes at least one of collagen, gelatin, chitosan, cellulose and its derivatives, starch and its derivatives, sodium alginate and xanthan gum.
4. The highly active and high-strength bio-based composite membrane according to claim 1, characterized in that: The interface compatibilizer includes at least one of carboxylated graphene, aminolated graphene and a silane coupling agent.
5. The highly active and high-strength bio-based composite membrane according to claim 1, characterized in that: The plasticizer is polyol and its ester derivatives.
6. The highly active and high-strength bio-based composite membrane according to claim 5, characterized in that: The plasticizer includes at least one of glycerol, sorbitol and isosorbide.
7. The highly active and high-strength bio-based composite membrane according to claim 1, characterized in that: The multivalent metal ions include at least one metal ion selected from the group consisting of aluminum, iron, cerium, gadolinium, praseodymium, and lanthanum.
8. The method for preparing a highly active and high-strength bio-based composite membrane according to any one of claims 1 to 7, characterized in that: After the raw materials are mixed evenly, they are reacted under ultrasonic stirring for 0.5 to 2 h at a pH of 2.0 to 4.5 and a temperature of 25 to 40 °C, and then a high-activity and high-strength bio-based composite membrane is prepared by a solution casting method.